Recontextualizing Orientalism in The Adaptation of Frank Herbert’s Dune into A Film by Denis Villenueve - Nadya Lazuardi (Fakultas Ilmu Budaya, 2024)
In this thesis, Dune, a novel written by Frank Herbert will be discussed through the perspective of adaptation and orientalism utilizing Hutcheon’s Theory of Adaptation and Edward Said’s Orientalism. This thesis endeavors to highlight the transformations of the adaptation from novel to film as well as proving the recontextualization of orientalism from the process of adaptation and the motive of the adaptation itself. This thesis uses qualitative research methodology. There are two categories of data. The primary data are taken directly from Frank Herbert’s Dune as well as from the film by Denis Villenueve. Secondary data are taken from books, websites, journals, and articles about Dune and orientalism. Debunking the transformation of the adaptation is a prominent first step in the discussion process. Figuring out which transformations related to orientalism needs some assistance from a supporting theory namely the storyworld-building theory. Through this perspective there are several points of transformation in the process of adaptation which are related to the recontextualization of orientalism, those are the existent of the characters and objects of the story as well as the distortion toward several significant event. Taking the result of the transformation of the adaptation into further analysis to prove the recontextualization of orientalism in the process of adaptation by means of Edward Said’s orientalism discourse. From this analysis, it was deliberately discovered that the context of orientalism in its initial form, the novel, and the adapted one, the film, is indeed different. The novel’s orientalism context laid bare within the blatantly amused orientalism which is mostly found in the imperialismlike discourse, whilst the adaptation takes a more contemporary route by sublimating the context of orientalism into a more general discourse of inclusivity in which fall shorts on many level of substance. The lack of substantial portrayal of the orientalism within the notion of the adaptation leads to a manipulative side of orientalism which positioned the occident as the ultimate savior of the orient. Out of the recontextualization of orientalism in the process of the adaptation, there are three main motives, which are intertwined with one another, discovered by means of Hutcheon’s Theory of Adaptation. Those motives are the Cultural Capital, Personal and Political, and Economic Lures.
Reupload File Repositori 20 Februari 2026_Teddy/Hendra
Keywords: Recontextualizing; Orientalism